Sprawl Angle in Simplified Models of Vertical Climbing: Implications for Robots and Roaches - Goran A. Lynch; Lawrence Rome; Daniel E. Koditschek (Applied Bionics and Biomechanics, 2011)
Empirical data taken from fast climbing sprawled posture animals reveals the presence of strong lateral forces with significant pendulous swaying of the mass center trajectory in a manner captured by a recently proposed dynamical template [1, 2]. In this simulation study we explore the potential benefits of pendulous dynamical climbing in animals and in robots by examining the stability and power advantages of variously more and less sprawled limb morphologies when driven by conventional motors in contrast with animal-like muscles. For open loop models of gait generation inspired by the neural-deprived regimes of high stride-frequency animal climbing, our results corroborate earlier hypotheses that sprawled posture may be required for stability. For quadratic-in-velocity power output actuation models typical of commercially available electromechanical actuators, our results suggest the new hypothesis that sprawled posture may confer significant energetic advantage. In notable contrast, muscle-powered climbers do not experience an energetic benefit from sprawled posture due to their sufficiently distinct actuator characteristics and operating regimes. These results suggest that the potentially significant benefits of sprawled posture climbing may be distinctly different depending upon the details of the climbers sensorimotor endowment. They offer a cautionary instance against mere copying of biology by engineers or rote study of physical models by biologists through this reminder of how even simple questions addressed by simple models can yield nuanced answers that only begin to hint at the complexity of biological designs and behaviors.